Fewer neurocognitive deficits and less brain atrophy by third ventricle measurement in PLWH treated with modern ART: A prospective analysis - Kaddu-Mulindwa, Dominic; Heit, Matthias; Wagenpfeil, Gudrun; Bewarder, Moritz; Fassbender, Klaus; Behnke, Stefanie; Yilmaz, Umut; Fousse, Mathias (Frontiers in Neurology, 2022)
Background Despite antiretroviral therapy cognitive dysfunction seems to remain a major issue for people living with HIV (PLWH). Previous studies showed a correlation between the width of the third ventricle (WTV) and neurocognitive disorders in PLWH. Patients and Methods We investigated prevalence and correlation of neuropsychological disorders using WTV as a brain atrophy marker examined by transcranial sonography and MRI in PLWH and healthy age- and gender matched controls. We used Becks Depression Inventory (BDI) for depression screening, the questionnaires Fatigue Severity Scale (FSS) for fatigue and Short-Form-36 (SF36) for quality of life (QoL) evaluation and Consortium to establish a registry for Alzheimer's disease (CERAD-PLUS) as neuropsychological test battery. Results 52 PLWH (47 males) and 28 non-infected controls (23 males) with a median age of 52 years (24 – 78 years) and 51 years (22 – 79), were analyzed. WTV correlated significantly with age (p < 0.01) but showed no significantly difference in PLWH (median = 3.4 mm) compared to healthy controls (median = 2.8 mm) (p = 0.085). PLWH had both significantly higher BDI-Scores (p = 0.005) and FSS-Scores (p = 0.012). Controls reported higher QoL (SF-36) with significant differences in most items. However, the overall cognitive performance (CERAD total score) showed no significant difference. The WTV of all subjects correlated with neurocognitive performance measured as CERAD total score (p = 0.009) and trail making tests A (p < 0.001) and B (p = 0.018). There was no correlation between the scores of BDI, FSS, SF-36, and CERAD-PLUS items and WTV. Conclusion WTV is considered as a predictor of cognitive deficits in neurodegenerative diseases. Nevertheless, we found no significant difference in WTV or overall cognitive performance between PLWH and controls. PLWH suffer more often from depression and fatigue and report reduced quality of life when compared to healthy controls.